Platelet-Activating Factor Receptor Ligands Protect Tumor Cells from Radiation-Induced Cell Death - da Silva-Junior, Ildefonso Alves; Dalmaso, Barbara; Herbster, Suellen; Lepique, Ana Paula; Jancar, Sonia (Frontiers in Oncology, 2018)
Irradiation generates oxidized phospholipids that activates Platelet-activating factor receptor (PAFR) associated with pro-tumorigenic effects. Here we investigated involvement of PAFR in tumor cell survival after irradiation. Cervical cancer samples presented higher levels of PAF receptor gene (PTAFR) when compared with normal cervical tissue. In cervical cancer patients submitted to radiotherapy the expression of PTAFR was significantly increased. Cervical cancer-derived cell lines (C33, SiHa, HeLa), and squamous carcinoma cell lines (SCC90 and SCC78) express higher levels of PAFR mRNA and protein than immortalized keratinocytes. Gamma radiation increased PAFR expression and induced PAFR-ligands and PGE2 in these tumor cells. Blocking of PAFR with the antagonist CV3938 before irradiation inhibited PGE2 and increased tumor cells death. Similarly, human carcinoma cell transfected with PAFR (KBP) were more resistant to radiation compared to those lacking the receptor (KBM). PGE2 production by irradiated KBP cells was also inhibited by CV3988. These results show that irradiation of carcinoma cells generates PAFR-ligands that protect tumor cells from death and suggests that the combination of radiotherapy with a PAFR-antagonist could be a promising strategy for cancer treatment.